Development of Antimicrobial Biopolymer Film Incorporated with a Mixture of Sodium Lactate and Diacetate and Studying its Efficacy Against Listeria monocytogenes and Microbiological Spoilage in Deli Meat Over 12 Weeks of Storage - Katherine Sierra; Luis Guzman; Vianca Tashiguano; Micah T. Black; Payten Leeds; Jakob Doster; Laura J. Garner; Sungeun Cho; Yucheng Peng; Amit Morey (Journal of Food Protection)
Food packaging is a major contributor to environmental pollution and is a concern among customers who are pushing the food industry towards innovative, sustainable, and biodegradable plastic-alternative packaging materials. The integration of biomolecules derived from agricultural waste has the potential to enhance the mechanical properties of these novel packaging materials. Additionally, incorporating antimicrobial agents can improve food safety and extend shelf life, thereby increasing the market acceptance of these environmentally friendly packaging solutions. Research was conducted to (1) develop and evaluate mechanical properties of plastic-alternative films with chicken skin gelatin and antimicrobials (a mixture of sodium lactate and sodium diacetate (LD)); and (2) evaluate the efficacy of the antimicrobial films against Listeria monocytogenes and microbiological spoilage of fully cooked, beef bologna. Through the 12-week storage, the LD biopolymer film initially exhibited bacteriostatic effects, followed by bactericidal (decrease of ∼2 log CFU/g), and again bacteriostatic effect on the pathogen during weeks 0–4, 5–6, and 7–12, respectively. The biopolymer film with antimicrobial reduced the spoilage microorganism’s growth by 0.6 log CFU/g over the 12-weeks of storage. Our research demonstrates that biopolymer films can be incorporated with antimicrobials and can be highly effective in controlling Listeria monocytogenes in ready-to-eat (RTE) meat products during storage.